Smart Learning Framework: Integration of Learning Theories and Instructional Design Models for the Development of Interactive Digital Media - Akhmad Dalil Rohman; Uki Adi Prasetiya; Tri Unggul Sari Asih; Rahmat Kamal (Papanda Publisher, 2026)
Learning in the digital era requires instructional media that not only deliver content effectively but also facilitate interactive and meaningful learning experiences. However, the development of digital media is often not grounded in strong theoretical foundations, both in terms of learning theories and instructional design models. This study aims to formulate the Smart Learning Framework as a conceptual synthesis that integrates learning theories and instructional design models for the development of interactive digital media. The study employs a library research approach through an in-depth review of scholarly articles, books, and relevant policy documents. Content analysis was used to identify the key contributions of behaviorism, cognitivism, and constructivism, as well as the characteristics of instructional design models including ADDIE, ASSURE, and Dick and Carey. The findings indicate that the three learning theories offer complementary perspectives in understanding learner behavior, cognitive processes, and knowledge construction, while the three instructional design models provide systematic, adaptive, and measurable frameworks for developing digital media. The synthesis of these two conceptual groups results in the Smart Learning Framework, which serves as a conceptual foundation for designing more effective and contextually relevant interactive digital media aligned with twenty-first century learning needs. The study concludes that the framework has the potential to improve instructional quality, although further implementation-based research is needed to empirically validate its effectiveness.